GREEN ACCOUNTING: THE CONCEPT OF ENVIRONMENTAL ECONOMICS AND ITS IMPLEMENTATION IN SUSTAINABLE ACCOUNTING PRACTICES - Khairul Mujahidi; Baiq Krisnina Maharani Putri; Ely Windarti Hastuti (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This study aims to explore the concept of green accounting within the framework of environmental economics and its application in sustainability-oriented accounting practices. Green accounting is an approach that seeks to integrate environmental factors into conventional financial reporting systems, with the main objective of increasing transparency of the impact of economic activity on the environment. The method used in this research is a literature study, by reviewing a number of literatures from scientific journals, academic books, and other relevant documents. The findings of this study indicate that green accounting can provide more comprehensive and socially accountable information to stakeholders, while supporting the achievement of the Sustainable Development Goals (SDGs). Nevertheless, the implementation of green accounting still faces various obstacles, such as the absence of standardized standards and resistance from business actors. Nevertheless, green accounting still has a strategic role in encouraging more environmentally sound and sustainable business practices.